Factors associated with polyp detection during colonoscopy: A retrospective observational study. Issue 9 (4th June 2019) - Chen, Chun‐Wei; Chiu, Cheng‐Tang; Su, Ming‐Yao; Lin, Chun‐Jung; Hsu, Chen‐Ming; Lim, Siew‐Na; Yeh, Chau‐Ting; Lin, Wey‐Ran
Abstract: The polyp detection rate (PDR) is an important quality indicator for colonoscopy. Several factors have been shown to be associated with PDR. However, whether the moderate sedation is a factor for polyp detection remains controversial. This study aims to assess factors associated with polyp detection including the moderate sedation factor during colonoscopy. Patients who underwent colonoscopy from June 1, 2014 to May 31, 2015 were enrolled into this retrospective study. Patients with poor colon preparation and failure to reach the cecum were excluded. The clinical factors, including patient's sex, age, midazolam/fentanyl sedation, indications, endoscopist colonoscopy volume, and use of antispasmodic agent were evaluated by multivariate analysis. A total of 3373 patients were included in this study. The mean age was 55.8 years, and 1980 patients (58.7%) were male. Among the 3373 patients, 2513 (74.5%) underwent midazolam/fentanyl‐based sedated colonoscopy. The multivariate analysis showed that male sex, age over 50 years old, midazolam/fentanyl sedation and indications of screening and surveillance were significantly associated with polyp detection. Moreover, when stratified by sex and age, the midazolam/fentanyl sedation was associated with polyp detection in male patients and patients over 50 years old. This study has highlighted the role of midazolam/fentanyl sedation administered by colonoscopists as a modifiable factor that may increase polyp detection during colonoscopy.